Identification and DNA sequence analysis of the Marek's disease virus serotype 2 genes homologous to the herpes simplex virus type 1 UL20 and UL21 - Hatama, S. (Tokyo Univ. (Japan)); Jang, H.K; Izumiya, Y; Cai, J.S; Tsushima, Y; Kato, K; Miyazawa, T; Kai, C; Takahashi, E; Mikami, T (Journal of Veterinary Medical Science, 1999)
We determined 3, 135 bp of the nucleotide sequence located in an 8.5 kb EcoRI-E fragment in the unique long (UL) genome region of Marek's disease virus serotype 2 (MDV2), and identified UL20 and UL21 homologous genes of herpes simplex virus type 1 (HSV-1). The UL20 and UL21 homologous genes of MDV2 are arranged colinearly with the prototype sequence of HSV-1. In addition, an open reading frame (MDV2 ORF 273), which has been identified within the UL21 homologous gene of MDV2, has no apparent relation to any other known herpesvirus genes. Northern blot analysis and reverse transcriptase polymerase chain reaction confirmed the existance of RNA transcripts related to the UL20 and ORF 273 genes in MDV2-infected cells, except no transcript related to the UL21 gene being detected. The putative protein product of the MDV2 UL20 gene had a relatively low homology but that of the MDV2 UL21 gene had a moderate homology among herpesviruses. Further, the possible functions and features of the predicted proteins encoded within the sequenced region are discussed.